Glomerular Diseases in Children - A Review of 27 Cases Recorded at a Single Centre in Eastern Nepal - Shrestha, P; Bhatta, NK; Tiwari, A; Singh, R; Kalakhetti, BK; Majhi, S; Paudel, P; Sinha, A (Journal of Nepal Paediatric Society, 2009)
Glomerular disease remains an important cause of renal disease in children. We retrospectively assessed the clinical features and histopathological diagnoses in kidney biopsy specimens in children (n=27). The medical records and histopathological diagnoses between 2003 and 2006 were reviewed. In each patient, clinical presentation, age at onset of disease, gender, presence of nephrotic range proteinuria, hematuria, hypertension and histopathological diagnoses were evaluated. SLE nephritis (n=8) and membranoproliferative glomerulonephritis (MPGN) (n=8) were the most frequent glomerular diseases and nephrotic syndrome (n=21) was the frequent clinical manifestation. Key words: Renal biopsy, Glomerular diseases doi:10.3126/jnps.v29i1.1597 J. Nepal Paediatr. Soc. Vol.29(1) p.26-29